Do employees' perceptions of HR practices in South African firms affect their subsequent turnover destinations? - Bussio, Stacy Katherine (My University, 2011)
Employee turnover is an ongoing issue in organisations because it has long been thought to detriment overall organisational efficiency and performance (Lee, Gerhart, Weller & Trevor, 2008; Takeuchi, Chen & Lepak, 2009; Trevor, 2001). Managers are only able to observe and control some aspects or influencers of turnover (Dalton, Todor & Krackhardt, 1982). Placing voluntary turnover drivers in context with human resource (HR) practices might provide a means through which managers can understand the less visible aspects of turnover. HR practices may assist managers to reduce the controllable (evident) and less observable drivers of voluntary turnover. March and Simon (1958), the seminal employee turnover theorists, suggest that the voluntary turnover decision has two competing aspects – desirability of the current job and desirability of alternatives. The perceived utility an employee garners from the current job might define the desirability of the current job. The more desirable the current job, the greater satisfaction and lower the likelihood of a quit. The potential utility the individual deems available from perceived alternative opportunities might define the desirability of alternatives. If the potential utility of an alternative outweighs the utility garnered by the current job, a quit seems more likely (March & Simon, 1958). Generally, mainstream voluntary turnover research has placed emphasis on understanding turnover antecedents in the current organisation - the aspects that lower the perceived utility garnered by the current job (Kirschenbaum & Weisberg, 2002). However, considerably less research has focused on the alternative that draws the employee away from their current job (Kirschenbaum & Weisberg, 2002). The alternative to which the individual moves is the turnover destination. The turnover destination contributes towards the withdrawal process because the person perceived the alternative as more desirable than the current job, increasing the likelihood of a quit. Observing organisational performance may provide an important means through which to examine the effect turnover destinations may have on withdrawal. Strategic human resource management (SHRM) and similar organisational development fields hold a particular view on organisational performance. SHRM theorists have paid particular attention to the implementation of high-performance human resource (HR) practices in organisations. Predominantly, extensive research has been conducted on the effect highiii performance HR practices might have on organisational performance and retention. SHRM theorists suggest that a combination (system) of high-performance HR practices correctly implemented in the firm, and aligned with organisational strategy, should bring about improved organisational performance and employee retention (Arthur, 1994; Carmeli & Schaubroeck, 2005; Combs, Liu, Hall & Ketchen, 2006; Shaw, Gupta & Delery, 2005; Subramony, 2009; Youndt, Snell, Dean & Lepak, 1996; Wood, 1999). The field of turnover destination research highlights the role of turnover destinations in the voluntary turnover process. Specifically, turnover destination theorists postulate that antecedents present in the current firm affect the quit decision by influencing the intensity of the desire to leave, and the perception of alternative opportunities shapes the choice of turnover destination (Kirschenbaum & Mano-Negrin, 1999; Kirschenbaum & Weisberg, 2002). Research in the field focuses on the influence turnover destinations might have on turnover intentions, moving away from the traditional focus of internal organisational antecedents and personal factors (Kirschenbaum & Weisberg, 2002). The relationship between high-performance HR practices and turnover destinations has not been extensively tested empirically, with few known studies in existence (for example: Fields, Dingman, Roman & Blum, 2005). Therefore, there is opportunity for greater research in the field. The developing South African economy is a suitable environment in which to measure whether high-performance HR practices affect turnover destinations at the individual-level, as no known research has been conducted. The South African economy is said to be suffering from the mass emigration of highly skilled individuals, who mostly move to developed countries with less prominent societal issues and less restrictive labour policies, amongst other reasons (Kerr-Phillips & Thomas, 2009; McDonald & Crush, 2002). A key interest for this research is the role experience of highperformance HR practices might play in emigration of South African white-collar workers. The study explores the relationship between high-performance HR practices and turnover destinations by measuring met expectations and turnover intentions. The objective of the empirical study is to establish whether experience of high-performance HR practices in the current job affect the likelihood of particular turnover destinations. A quantitative study, using a two-part time-separated survey, was conducted on white-collar workers from three South African provinces, including Gauteng, Kwa-Zulu iv Natal and the Western Cape. The first part of the survey measured respondents’ perceptions of the levels of actual high-performance HR practice provision in the current organisation. In addition, respondent expectations about the adequate level of the practices (that should retain them in their current jobs) were measured. The second part of the survey measured respondents’ intentions to move into a predefined set of turnover destinations. The final sample of 386 participants was used to analyse the impact of interactions between actual and adequate high-performance HR practices on a variety of turnover destinations, using polynomial regression analysis and response surface methodology. Overall, the results showed that a system of high-performance HR practices exert a weak to moderate influence on the predefined turnover destinations. Generally, South Africans with lower expectations about high-performance HR practice provision appear less likely to leave a job when the employer places greater emphasis on the practices. However, the likelihood of internal transfer and moving into a different organisation increases for individuals who possess higher expectations about high-performance HR practice provision, and have experienced higher levels of actual provision. The findings also show that, for the most part, the likelihood of emigration increases in employees with lower actual provision of high-performance HR practices, largely contradicting expectations about emigration. The increase in the likelihood of internal transfers and moves to external organisations, despite higher actual high-performance HR practice provision, might point towards over-provision of the practices, or the possibility of continuance commitment in South African employees. The findings suggest that, rather than higher emphasis of highperformance HR practices providing a means for emigration, broader external societal conditions may be motivating the emigration of skilled South Africans. As the results showed that a set of high-performance HR practices may exert a weak to moderate influence on turnover destination selection, there are recommendations for managers and future research. Implications for managers include promoting the implementation of a set of high-performance HR practices in the organisation. Researchers in the turnover destinations field should endeavour to measure actual turnover, rather than intentions in future studies.
Keywords: Human resource management; Employee turnover; Organisational performance; Turnover destinations; South Africa